f( θ)= ( θ+1)cos θ
f'( θ)=(1)-sin θ
f"9 θ)=-sin θ
Is this correct?
Oops. Sorry about that! I meant use the 'product rule'. Which is exactly what I posted.
$\displaystyle
\begin{gathered}
f(\theta ) = (\theta + 1)\cos \theta \hfill \\
u = (\theta + 1) \hfill \\
v = \cos \theta \hfill \\
f(\theta ) = u \cdot v \hfill \\
f'(\theta ) = u'v + uv' \hfill \\
f'(\theta ) = 1 \cdot \cos \theta + (\theta + 1) \cdot - \sin \theta \hfill \\
f'(\theta ) = \cos \theta - \theta \sin \theta - \sin \theta \hfill \\
\end{gathered}
$